Optical Simulation of Planar CH3NH3PbI3 Perovskite Solar Cells - Duc Cuong, Nguyen (VNU Journal of Science: Mathematics - Physics, 2019)
This article presents optical simulation results of planar CH 3 NH 3 PbI 3 solar cells using a MATLAB script developed by McGehee’s group (Stanford University). The device structure is composed of FTO/HEL/AL/EEL/LiF/Al, where HEL is the hole-extraction layer, AL is the active layer (CH 3 NH 3 PbI 3 ), and EEL is the electron-extraction layer. In this MATLAB script, the transfer matrix method was used, where transmission and reflection were calculated for each interface in the stack as well as attenuation in each layer. The wavelength-dependent optical constants ( n and k ) of each layer were measured by spectroscopic ellipsometry (SE). The exciton generation rates within the active layer were calculated based on the data of optical constants, as well as the thickness of each layer. Considering the Internal Quantum Efficiency (IQE) equal to 100% at all wavelengths, the predicted short-circuit currents ( J SC ) were also estimated. The obtained results show a good agreement with the experimental values of J SC measured on real devices.